CONCRETE STRENGTH DETERMINATION USING MICROSTRIP PATCH ANTENNA VIA VECTOR NETWORK ANALYZER - Benjamin, Emin (Universiti Malaysia Sarawak (UNIMAS), 2023)
Compressive strength of concrete is very important to provide good quality of concrete, ensuring public safety and increase the lifespan of concretes. One of the most important parameters influencing the concrete strength is moisture content. This project proposed a portable microwave non-destructive method by designing a microstrip patch antenna operating at 2.4 GHz using Computer Simulation Technology (CST) Studio Suite. The microstrip patch antenna is connected to Vector Network Analyzer (VNA) via coaxial cable to obtain the reflection coefficient. The reflection coefficient will be correlated with moisture content and compressive strength of concrete cubes. The microstrip antenna will be investigated on the reliability of concrete strength determination. The initial results of antenna when projecting the signal into open air yields a -33.38 dB and frequency of 2.566 GHz which is within the acceptable range of planned frequency. Two experiments are conducted which are concrete cubes cured for 28 days and concrete cubes with various moisture content. Relationship of reflection coefficient with curing time and compressive strength are obtained in this first experiment while relationship between reflection coefficient and moisture content are obtained from the second experiment. The value of moisture content varies from 0% to 45% are tested and measured using the microstrip patch antenna. Two equations are obtained from the relationship between reflection coefficient with moisture content and compressive strength. From the equations, the accuracy in prediction of moisture content and compressive strength is 93.37% and 97.43% respectively. Hence the equations show great potential of the microwave method in determination of compressive strength of concrete cubes.